2020
DOI: 10.1111/apt.15773
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the signalling and functional role of the extracellular matrix in the development of liver fibrosis

Abstract: Summary Background Patients with liver fibrosis show a large heterogeneity, and for that reason effective treatments are still lacking. Emerging data suggest that there is more to fibrosis than previously understood. Opposed to earlier belief of being a passive scaffold for cells to reside in, the extracellular matrix (ECM) is now known to hold both signalling and functional properties important for the development of fibrosis. The interaction between the ECM and the collagen‐producing cells determines the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 133 publications
(245 reference statements)
0
23
0
Order By: Relevance
“…The physical and chemical properties of the environment, in which HSCs are embedded, are also important for their activation (34), at least partly via Src and RhoA pathways (35). The majority of the fibrotic material is synthesized by HSC, and together with other cells they contribute to the perpetuated remodelling of the matrix, reviewed elsewhere (36,37). The stiffness of the matrix is provided, among other J o u r n a l P r e -p r o o f mechanisms, by the crosslinking of collagens, which leads to a less reversible fibrosis (38).…”
Section: Stiffnessmentioning
confidence: 99%
“…The physical and chemical properties of the environment, in which HSCs are embedded, are also important for their activation (34), at least partly via Src and RhoA pathways (35). The majority of the fibrotic material is synthesized by HSC, and together with other cells they contribute to the perpetuated remodelling of the matrix, reviewed elsewhere (36,37). The stiffness of the matrix is provided, among other J o u r n a l P r e -p r o o f mechanisms, by the crosslinking of collagens, which leads to a less reversible fibrosis (38).…”
Section: Stiffnessmentioning
confidence: 99%
“…[29À31] Moreover, the production of hydrogen peroxide by QSOX1 in the extracellular space may trigger inflammation [32]. With modulation of extracellular matrix being a hallmark of liver fibrosis and with hepatic stellate cells and portal fibroblasts being important sources of matrix proteins in hepatic fibrosis [33,34], it is possible that secreted QSOX1 is related to physiological responses to CLD. An important question is why the DOC assay shows better performance than the SOX assay, as both assays measure QSOX1-like activity.…”
Section: Discussionmentioning
confidence: 99%
“…Type VI collagen is a microfibrillar collagen found between the IM and the BM that can stimulate the proliferation of mesenchymal cells [ 66 , 67 ]. During liver fibrosis, it has been found that collagen VI is up to tenfold induced in liver fibrosis [ 68 ], and its signaling peptide endotrophin plays a crucial role in fibrosis.…”
Section: Ecm Components Implicated In Remodelingmentioning
confidence: 99%